Psychosocial wellbeing among children and adults with arthrogryposis: a scoping review - Sarah Cachecho (BMC, 2021)
Abstract Background Arthrogryposis multiplex congenita (AMC) is a group of congenital conditions characterized by joint contractures in two or more body areas. Management of AMC starts early in life and focuses on improving mobility and function through intensive rehabilitation and surgical interventions. Psychosocial wellbeing is an important determinant of health and the psychosocial experience of individuals with AMC should be considered in the management of this condition. The aim of this scoping review was to explore what is known about the psychosocial wellbeing of children and adults with AMC, to identify the outcome measures used and to explore the factors associated with psychosocial outcomes in this population. Methods A comprehensive search in four databases was conducted. Articles discussing psychosocial outcomes and outcome measures used with children or adults with AMC were included. Data on the measures used, psychosocial outcomes, and factors associated with psychosocial outcomes, were extracted and analyzed descriptively and synthesized narratively. Results Seventeen articles were included in this scoping review, ten including the pediatric population, six including adults and one article including both children and adults with AMC. The most commonly used outcome measures were the PODCI in the pediatric studies, and the SF-36 in studies on adults. In the pediatric studies, psychosocial outcomes were often secondary, compared to the studies on adults. Results showed that in both children and adults, psychosocial outcomes are comparable with the levels of the general population. Qualitative studies reflected the affective needs of this population and issues with emotional wellbeing. Factors such as fatigue and pain were associated with poorer psychosocial outcomes in adults with an impact on social relationships, intimacy and family planning. Conclusion Validated outcome measures, qualitative approaches and longitudinal studies are needed to better understand the psychosocial outcomes in AMC over time. Psychosocial support should be part of the multidisciplinary management of AMC throughout the lifespan.